2020
DOI: 10.1371/journal.pone.0240006
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody prevalence in health care workers: Preliminary report of a single center study

Abstract: Serological surveys have been conducted to establish prevalence for COVID-19 antibodies in various cohorts and communities, reporting a wide range of outcomes. The prevalence of such antibodies among healthcare workers, presumed at higher risk for infection, has been increasingly investigated, more studies are needed to better understand the risks and infection transmission in different healthcare settings. The present study reports on initial sero-surveillance conducted on healthcare workers at a regional hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
5
23
2
Order By: Relevance
“…Similar to our data, several studies reported low seroprevalences among HCWs 19 21 . For example, in Greek where the prevalence of COVID-19 was only 0.12%, the overall seroprevalence in 1495 HCWs in two hospitals was 1.26% (95% CI 0.43, 3.26) 19 .…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our data, several studies reported low seroprevalences among HCWs 19 21 . For example, in Greek where the prevalence of COVID-19 was only 0.12%, the overall seroprevalence in 1495 HCWs in two hospitals was 1.26% (95% CI 0.43, 3.26) 19 .…”
Section: Discussionsupporting
confidence: 92%
“…The present study found a considerably lower adjusted antibody prevalence (0.98%) on initial sampling (95.9% blood drawn during a “shelter at home” mandate in May–June 2020) among HCWs, confirming our initial findings [ 20 ] in a larger cohort. The community prevalence during this early period was relatively low (3.64%), as reflected by those tested by physician order in our community, and also reflected in adjusted prevalence among the first responders tested in this study (5.75%), though both these prevalence results were considerably higher than that of our HCWs.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous study, conducted during a “shelter at home” mandate in May–June 2020, observed an antibody prevalence of 1.06% (adjusted antibody prevalence for test sensitivity and specificity of 1.13%) among our HCWs (n = 2924) at Hoag Memorial Hospital Presbyterian, Orange County, California. This was much lower than those reported by other studies [ 20 ]. Therefore, to further analyze the evolving prevalence of antibodies among HCWs, the present study expands our initial study in a larger HCW cohort and also reports on 8-week follow-up to investigate the longevity of antibody presence.…”
contrasting
confidence: 66%
“…Overall SARS-CoV-2 seroprevalence of 24.4% in HCWs was significantly greater than the 6% seroprevalence in the general population of the Midlands region, according to data published by Public Health England which suggests a marked occupational risk of exposure for HCWs during the COVID-19 pandemic [9]. Another study found 13.7% IgG prevalence among 40,329 HCWs in the greater New York City area similar to the community prevalence in New York State (14.0%) [15]. Hains et al [18] reported a seroconversion in 44.0% (n=11/25) of HCWs at a dialysis unit in America.…”
Section: Discussionmentioning
confidence: 92%
“…Variable seroreactivity has been reported in the literature, ranging from 57% prevalence in Bergamo-Italy's epicenter, 20% in New York City, 5.2% in Kenya, to a low percentage of 4.7% in Los Angeles County and 2.8% in Santa Clara County California [10,[14][15][16][17]. Overall SARS-CoV-2 seroprevalence of 24.4% in HCWs was significantly greater than the 6% seroprevalence in the general population of the Midlands region, according to data published by Public Health England which suggests a marked occupational risk of exposure for HCWs during the COVID-19 pandemic [9].…”
Section: Discussionmentioning
confidence: 99%